Soil mycoflora of banana and cassava in peatland and alluvial soil in Bengkulu (Biodiversitas Journal of Biological Diversity, 2006)
In order to discover the diversity and population of soil fungi, a study was carried out at banana (Musa paradisiaca) and cassava (Manihot utilissima) plants where both those plants planted in peatland and alluvial soil. Soil fungi were isolated using serial dilution plate method and they were incubated at both room temperature (27-28oC) and 45oC. This process was replicated two times for each sample. The result indicated that from 4 soil samples, 24 genera of fungi representing 4 Ascomycotina, 15 Deuteromycotina, and 5 Zygomycotina weredetected. The highest soil fungi population was found in cassava planted in peat land and incubated at room temperature (8.5 105 cfu/ g dry soil), while the lower soil fungi population came from banana plant that was planted in peat land and incubated at 45oC (7.1 103 cfu/g dry soil).ô€‚” 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: banana, cassava, peatland, alluvial soil, soil fungi.